Cross-correlation and time history analysis of laser dynamic specklegram imaging for quality evaluation and assessment of certain seasonal fruits and vegetables. (19th September 2017) - Samuel, Boni; Retheesh, R; Ansari, Md Zaheer; Nampoori, V P N; Radhakrishnan, P; Mujeeb, A
Abstract: Quality evaluation of fruits and vegetables is of great concern as there is a shortage of unadulterated items on the market. Even unadulterated fruits and vegetables, especially those with soft tissue, cannot be stored for longer times due to physical and chemical changes. Moreover, damage can occur during harvest and in the post-harvest period, while preserving or transporting the fruits and vegetables. This work describes the use of a laser dynamic speckle imaging technique as a powerful optoelectronic tool for the quality evaluation of certain seasonal fruits and vegetables in an Indian market. A simple optical configuration was designed for developing the dynamic speckle imagining system to record dynamic specklegrams of the specimens under different conditions. These images were analysed using a cross-correlation function and the temporal history of specklegrams. The technique can be effectively adapted to the industrial environment and would be beneficial for all stakeholders in the field.